Music and gender in the sub-arctic Algonkian area - Diamond, Beverley (Women in North American I[*****] Music: Six Essays, 1989)

The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

Sémiologie des jeux vocaux Inuit - Nattiez, Jean-Jacques (Semiotica, 1987)
Keywords: Pas de lien web

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Some Aspects of Inuit Vocal Games - Nattiez, Jean-Jacques (Ethnomusicology, 1983)

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

Comparisons within a Culture: The Example of the Katajjaq of the Inuit - Nattiez, Jean-Jacques (Cross-Cultural Perspectives on Music, 1982)

Pour l'adéquation de la transcription en ethnomusicologie : l'exemple du katajjaq - Berthiaume-Zavada, Claudette (Canadian University Music Review, 1980)
Keywords: Music